2008
DOI: 10.1158/0008-5472.can-08-0377
|View full text |Cite
|
Sign up to set email alerts
|

A Feed-Forward Loop Involving Protein Kinase Cα and MicroRNAs Regulates Tumor Cell Cycle

Abstract: Protein kinase CA (PKCA) has been implicated in cancer, but the mechanism is largely unknown. Here, we show that PKCA promotes head and neck squamous cell carcinoma (SCCHN) by a feed-forward network leading to cell cycle deregulation. PKCA inhibitors decrease proliferation in SCCHN cell lines and xenografted tumors. PKCA inhibition or depletion in tumor cells decreases DNA synthesis by suppressing extracellular signal-regulated kinase phosphorylation and cyclin E synthesis. Additionally, PKCA down-regulates mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…S1), an Illumina cohort (Yordy and colleagues; unpublished results), and two Affymetrix cohorts (9,11). These crossplatform datasets were used as the discovery set for the classification of HNSCC samples.…”
Section: Identification and Validation Of Three Hnscc Supergroupsmentioning
confidence: 99%
“…S1), an Illumina cohort (Yordy and colleagues; unpublished results), and two Affymetrix cohorts (9,11). These crossplatform datasets were used as the discovery set for the classification of HNSCC samples.…”
Section: Identification and Validation Of Three Hnscc Supergroupsmentioning
confidence: 99%
“…Through a cell-autonomous loop BMP-4 and BMP-7 engage BMP-RI to sustain or amplify Smad signal transduction, ultimately promoting expression of SOX9 and downstream aggrecan and collagen II genes. B, in a feedforward circuit A activates B, and A and B activate C (42). C, we propose that LPP initiates a feedforward circuit in which A is represented by BMP-RII, B by BMP-RI, and C by Smad1/5.…”
Section: Discussionmentioning
confidence: 87%
“…Expression of miR-15a was inversely correlated with protein kinase C which was usually overexpressed in primary HNSCC (Cohen et al, 2009). It has been shown that overexpression of miR-15a suppressed cyclin E protein expression and inhibition of miR-15a enhanced cyclin E protein expression in laryngeal cancer cell line.…”
Section: Mir-15a [Mature Sequence: 14 -Uagcagcacauaaugguuugug -35 (Mimentioning
confidence: 99%
“…It has been shown that overexpression of miR-15a suppressed cyclin E protein expression and inhibition of miR-15a enhanced cyclin E protein expression in laryngeal cancer cell line. Precursor miR-15a could also affect DNA synthesis in laryngeal carcinoma cells but the related mechanisms are not yet identified (Cohen et al, 2009). These results indicated that miR-15a might function as a tumor suppressor through regulating the gene associated with the proliferation pathways of cancer cells (Cohen et al, 2009).…”
Section: Mir-15a [Mature Sequence: 14 -Uagcagcacauaaugguuugug -35 (Mimentioning
confidence: 99%